Indenoquinaldine-based unsymmetrical squaraine dyes for near-infrared absorption: investigating the steric and electronic effects in dye-sensitized solar cells - Bisht, Rajesh; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Chemistry-A European Journal, 2018)
A series of near-infrared (NIR)-responsive unsymmetrical squaraine dyes (ISQ1-3) incorporating a fused indenoquinaldine-based donor have been designed and synthesized. C-12 alkyl chains were incorporated at the sp(3)-hybridized carbon center of the indene unit of the indenoquinaldine in an out-of-plane orientation to control dye aggregation on the surface of titanium dioxide, and indole (ISQ1), benzo[e]indole (ISQ2), and quinoline (ISQ3) moieties were included as the donor component bearing the anchoring carboxy group to extend the absorption in the NIR region and to systematically study the effect of the electronic modification on the performance of dye-sensitized solar cells (DSSC). All the dyes exhibit intense absorption (epsilon >= 10(5) m(-1) cm(-1)) in the NIR region, and the dye-adsorbed TiO2 films exhibit broad panchromatic absorption. The incident photon-to-current efficiency (IPCE) spectrum of the ISQ3-based DSSC device displays a panchromatic IPCE response up to 880 nm. Additionally, the ISQ3-sensitized device provides the best efficiency of 4.15% with a short circuit current density (J(SC)) of 10.02 mA cm(-2), open-circuit voltage (V-OC) of 0.58V, and fill factor (ff) of 72% in the presence of 10 equivalents of 3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid (CDCA). Electrochemical impedance spectroscopy analysis showed attenuated charge recombination in the ISQ3-sensitized DSSC, which contributes to its higher value of V-OC compared with the other dyes.